2019
DOI: 10.1016/j.dib.2019.103701
|View full text |Cite
|
Sign up to set email alerts
|

Translatome and transcriptome analysis of TMA20 (MCT-1) and TMA64 (eIF2D) knockout yeast strains

Abstract: TMA20 (MCT-1), TMA22 (DENR) and TMA64 (eIF2D) are eukaryotic translation factors involved in ribosome recycling and re-initiation. They operate with P-site bound tRNA in post-termination or (re-)initiation translation complexes, thus participating in the removal of 40S ribosomal subunit from mRNA stop codons after termination and controlling translation re-initiation on mRNAs with upstream open reading frames (uORFs), as well as de novo initiation on some specific mRNAs. Here we report r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In Saccharomyces cerevisae , the homologs of eIF2D , DENR, and MCTS-1 (Tma64 Tma22, and Tma20, respectively) have more prominent roles in ribosome recycling as evidenced by increased translation of downstream of ORFs and uORFs 58 . The translation of GCN4, the S. cerevisiae equivalent of ATF4, also increases upon the loss of these recycling factors 59 . Together, these findings suggest that the in vivo roles of eIF2D, DENR, and MCTS have diverged during evolution, with metazoan factors playing more prominent roles in translational initiation of ATF4 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisae , the homologs of eIF2D , DENR, and MCTS-1 (Tma64 Tma22, and Tma20, respectively) have more prominent roles in ribosome recycling as evidenced by increased translation of downstream of ORFs and uORFs 58 . The translation of GCN4, the S. cerevisiae equivalent of ATF4, also increases upon the loss of these recycling factors 59 . Together, these findings suggest that the in vivo roles of eIF2D, DENR, and MCTS have diverged during evolution, with metazoan factors playing more prominent roles in translational initiation of ATF4 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report revealed that co-deletion of the yeast eIF2D (Tma64) and a ribosome recycling factor (Tma20 or Tma22) results in translation reinitiation at downstream AUG codons after translation termination and hence promotes translation of uORF-containing reporters [118]. Moreover, eIF2D knockout altered ribosome profiling reads in uORFs of GCN4, suggesting a regulatory role for eIF2D in translation of uORFcontaining mRNAs [119]. Whether cell stress or oncogenic signaling modulates the activity of these factors and hence influences uORF activation or CDS translation remains to be investigated.…”
Section: Heterogeneity Of the Translation Machinerymentioning
confidence: 99%
“…However, it has become clear that these marker insertions and analyses for TPE for example may be difficult [27]. Also, marker insertion at any location in the genome can affect the transcriptional potential of an area surrounding the marker and hence the chromatin configuration may not reflect that of the native state [28]. Genome wide analyses of nucleosome positioning suggested a low content of nucleosomes across the X elements [29], whereas a parallel study suggested positioned nucleosomes over those same areas [30].…”
Section: Introductionmentioning
confidence: 99%